Analysis of behaviour change ideological dynamics beyond open defecation free certification: A pathway to sustainable sanitation in Balaka, Malawi. - Kamwana, Laston (My University, 2026)
Malawi adopted the Community-Led Total Sanitation behaviour-change approach to align with global sanitation standards and eliminate open defecation. Balaka became the first Open Defecation-Free (ODF) Model District, achieving latrine and hand-washing facility (HWF) usage rates above the 95% national guideline. However, within a year, the district experienced an 11% ODF slippage, raising concerns about the sustainability of behaviour change. This study assessed post-ODF behaviour change dynamics by examining community knowledge, attitudes, practices, stages of change, and change determinants. A descriptive cross-sectional mixed-methods design was guided by the SaniFOAMS framework, the Socio-Ecological Model, and the Trans-theoretical Model of Behaviour Change. Data were collected through household interviews, key informant interviews, focus group discussions, and direct observations. Quantitative data were analyzed using Excel and SPSS (V.25), while qualitative data underwent thematic analysis. Binary logistic regression and Chi-square tests assessed associations and predictors of ODF sustainability. Findings show that although communities demonstrated adequate CLTS knowledge and positive attitudes towards ODF, key hygiene indicators fell below national standards. Pit latrine coverage (89%) and usage (95.7%) were relatively high, yet HWF availability (36.5%) and hand-washing with soap (HWWS) (24.9%) remained far below the 95% guideline. Limited commitment to HWF construction and HWWS after defecation was the gap. Personal, social, technical, institutional, cultural, and religious factors significantly influenced HWF construction and HWWS (p < 0.05), while cultural and religious beliefs also affected latrine usage (p < 0.05). Overall, progression in hygiene-related behaviour change was minimal. Strengthening skills, improving access to construction materials and enhancing routine monitoring, ODF re-verification and re-certification are critical to reinforce and sustaining behaviour change post ODF-certification in Balaka.